Association of body mass index with lifestyle and rotating shift work in Japanese female nurses. (23rd September 2014) - Tada, Yuki; Kawano, Yukari; Maeda, Izumi; Yoshizaki, Takahiro; Sunami, Ayaka; Yokoyama, Yuri; Matsumoto, Harumi; Hida, Azumi; Komatsu, Taiki; Togo, Fumiharu
<x xml:space="preserve">Abstract</x> Objective Higher body mass index (BMI) values have been reported in rotating shift workers compared with regular daytime workers. This study examines the relationship between work schedule and BMI, and considers whether lifestyle habits could explain the relationship. Methods Japanese female nurses (1179 day workers and 1579 rotating shift workers, aged 20‐59) were studied using self‐administered questionnaires. The questionnaires assessed height, weight, and dietary intake, physical activity, and sleep (lifestyle) habits. Results The BMI of shift workers was significantly higher than that of day workers. Shift workers consumed significantly higher amounts of sugar‐sweetened beverages and slept for significantly shorter durations on nights between days on the day shift compared with day workers—factors which were also independently associated with higher BMI. In addition, multivariable linear regression coefficients for BMI showed a significant correlation with rotating shift work (β = 0.051), after controlling for lifestyle habits. Conclusions Higher consumption of sugar‐sweetened beverages and shorter sleep duration were associated with rotating shift work and higher BMI. This should be taken into consideration in preventing obesity in real‐life shift work situations. Other shift work‐related factors, such as abnormal timing of meals and/or sleep, should also be identified.